Prescribing of nonsteroidal anti-inflammatory drugs, tramadol, and opioids in children: Patterns of its utilization - Zin, Che Suraya (Wolters Kluwer Medknow Publications, 2020)
Background: Analgesic is commonly used in children but little is known about its patterns of utilization. This study explored the patterns of analgesic prescribing in children. Materials and Methods: This cross-sectional study used prescription databases of tertiary hospital settings in Malaysia from 2010 to 2016. Prescriptions for nine NSAIDs (diclofenac, ketoprofen, etoricoxib, celecoxib, ibuprofen, indomethacin, mefenamic acid, meloxicam, and naproxen), tramadol, and five other opioids (morphine, oxycodone, fentanyl, buprenorphine, and dihydrocodeine) prescribed for children aged <18 years were included. Number of annual patients and prescriptions were measured and analyzed using Stata v15. Results: During a 7-year study period, a total of 5040 analgesic prescriptions of the nine NSAIDs, tramadol, and five other opioids were prescribed for 2460 pediatric patients (81.8% NSAIDs patients, 17.9% tramadol patients, and 0.3% opioid patients). Ibuprofen was the primary analgesic in young children less than 12 years old (≤2 years old [y.o.] [75%], 3–5 y.o. [85%], and 6–12 y.o. [56.3%]). However, there was a wide range of analgesics used in older children (>12 y.o.) with the majority for naproxen (13–15 y.o. (28.2%) and 16–17 y.o. (28.2%). Other frequently prescribed analgesics for older children included ibuprofen (20.6%) and diclofenac (18.2%) for 12–15 y.o. and diclofenac (26.7%) and tramadol (17.6%) for 16–17 y.o. Conclusion: Ibuprofen was the primary analgesic for children less than 12 y.o., whereas there was a wide range of analgesics prescribed for children age >12 y.o. including naproxen, diclofenac, and tramadol.